2020
DOI: 10.3389/frobt.2020.00002
|View full text |Cite
|
Sign up to set email alerts
|

Marine Applications of the Fast Marching Method

Abstract: Path planning is general problem of mobile robots, which has special characteristics when applied to marine applications. In addition to avoid colliding with obstacles, in marine scenarios, environment conditions such as water currents or wind need to be taken into account in the path planning process. In this paper, several solutions based on the Fast Marching Method are proposed. The basic method focus on collision avoidance and optimal planning and, later on, using the same underlying method, the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…An improved anisotropic fast marching method using a multi-layered fast marching was proposed by Song, Liu & Bucknall (2017), which combines different environmental factors and provides interesting results. In addition to the global path planning, the FMM-based methods also show potential in collision avoidance of USVs (Wang, Jin & Er, 2019;Garrido, Alvarez & Moreno, 2020). These successful studies have demonstrated the potential of FMM-based methods in global path planning of USVs.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…An improved anisotropic fast marching method using a multi-layered fast marching was proposed by Song, Liu & Bucknall (2017), which combines different environmental factors and provides interesting results. In addition to the global path planning, the FMM-based methods also show potential in collision avoidance of USVs (Wang, Jin & Er, 2019;Garrido, Alvarez & Moreno, 2020). These successful studies have demonstrated the potential of FMM-based methods in global path planning of USVs.…”
Section: Introductionmentioning
confidence: 90%
“…FMM-based methods have been widely used in path planning applications (Gómez et al, 2013;Amorim & Ventura, 2014;Alvarez et al, 2015;González et al, 2016). Marine applications based on FMM were introduced by Garrido, Alvarez & Moreno (2020). Interesting modifications for the FM 2 method have been performed, and the FMM has been subjected to a vector field considering the effects of several vector variables such as wind flow or water currents (Garrido, Alvarez & Moreno, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance calculated at each iteration is compared with the distance of each previous iteration. A priority queue is generated where the shortest distances are given priority [75]. An update in distance is defined as:…”
Section: Geodesic Distancementioning
confidence: 99%